Sea cucumber (Echinodermata: Holothuroidea) species richness at selected localities in Malaysia - Kamarudin K.R.; Usup G.; Hashim R.; Maryam Mohamed Rehan (Universiti Putra Malaysia, 2024)
Indexed by Scopus